Bringing modernity to prosocial crowdfunding’s campaigns: An empirical examination of the transition to modern sectors - Gama, Ana Paula Matias (2021)
This study addresses the successive calls to better understand the contexts of crowdfunding as well as the interplay between social and financial factors in driving lender decisions by deploying economic development theory inspired on the two-sector model. Making recourse to the leading prosocial crowdfunding platform KIVA, this study examines the impact of the business-loan purpose (traditional vs modern) on the success of fundraising campaigns. The results indicate how modern-sector business loan campaigns lead to faster funding from crowdfunding campaigns. Furthermore, when directed towards modern sectors, large loans emerge as more appealing to lenders, indicating how large loans go to financing high-return projects. Female microentrepreneurs gain an advantage over men in both the traditional and modern sectors. However, the comparative advantage of female microentrepreneurs becomes less pronounced among modern-related loan campaigns. Overall, the findings support how the global crowdfunded microfinance ecosystem boosts the transition of poor microentrepreneurs to a modern economy and thereby avoiding development traps, and thus also providing theoretical insights into predicting prosocial lending decisions regarding sectoral choices.